Self-supplied liquid injection field desorption/ionization ion source for an orthogonal time-of-flight instrument - Linden, Mathias H.; Linden, H. Bernhard; Nieth, Norbert; Gross, Jürgen H. (Journal of the American Society for Mass Spectrometry, 2019)
A new implementation of a dedicated ion source for field ionization (FI), field desorption (FD), and liquid injection field desorption/ionization (LIFDI) for the JEOL AccuTOF GC series of orthogonal-acceleration time-of-flight instruments is presented. In contrast to existing implementations, this third-party LIFDI probe and source combination does not require the exchange of the entire ion source comprising ion source block and lens stack to switch from electron ionization (EI) to LIFDI. Rather, the methods may be swapped conveniently by only exchanging the ion source block for a mechanical probe guide and inserting the LIFDI probe in place of the standard direct insertion probe (DIP) via the vacuum lock. Further, this LIFDI setup does not require any changes of the electronics or software of the AccuTOF mass spectrometer because it is self-supplied in terms of power supply, observation optics, and computer control. The setup offers advanced FI/FD/LIFDI control features such as emission-controlled emitter heating current and emitter flash baking during elongated runs as required for gas chromatography-FI-mass spectrometry (MS). The LIFDI source and probe and its operation are reported in detail. FI spectra of the volatile analytes toluene, heptane, and pentafluoroiodobenzene are presented. LIFDI operation is demonstrated for the analysis of the saturated hydrocarbon dotriacontane and the low-mass hydrocarbon polymers polystyrene 484 and polystyrene 1050. Further, the air-sensitive 2nd-generation Hoveyda-Grubbs catalyst is analyzed by LIFDI-MS. For comparison with long-established LIFDI instrumentation, some of the spectra obtained with the new setup are also compared with those from a double-focusing magnetic sector instrument. Open image in new window